Late Holocene temporal constraints for human occupation levels at the Bodo archaeological locality, east-central Alberta, Canada using radiocarbon and luminescence chronologies. (May 2014) - Munyikwa, Kennedy; Gilliland, Krista; Gibson, Terrance; Mann, Elizabeth; Rittenour, Tammy M.; Grekul, Christie; Blaikie-Birkigt, Kurtis
Abstract : The Bodo Archaeological Locality in east-central Alberta is one of the largest precontact (prehistoric) archaeological sites in the Canadian Prairie Ecozone. Situated at the transition between the aspen parkland and fescue grassland regions within a postglacial eolian dune landscape, the site has the potential to add to existing understandings of cultural–environmental dynamics as they relate to late Holocene hunter-gatherer settlement and subsistence patterns in the region. To that end, we present a composite stratigraphy for the locality constructed from five separate sampling pits, obtaining chronological control using accelerator mass spectrometry radiocarbon and luminescence ages. We identify three main periods of landscape stability and associated human occupation during the late Holocene: 750 to 400 cal B.C., 750 to 1000 cal A.D., and 1450 to 1750 cal A.D. Early Holocene eolian activity is documented, but the mid-Holocene stratigraphic record is absent, suggesting extensive sediment reworking. Evidence also exists of major cultural landscape changes that coincide with the arrival of Euro-Canadians.